Clear-water scour at a side-weir intersection along the bend - Agaçcioglu, H; Önen, F (WILEY, 2005)
The present study focuses on the local depth of clear-water scour at a side-weir intersection located on the curved part of an alluvial channel for each 30 degrees angle along the bend. At the downstream end of the side-weir, a longitudinal bar in the middle of the channel and a scour hole close to the outer bank are formed because of the changes in shear stress field and velocities. The depth of clear-water scour approaches the equilibrium depth of scour asymptotically with time, depending on flow intensity. It was also found that the equilibrium depth of scour depends on the dimensionless parameters of flow intensity, flow shallowness, weir crest height, side-weir length and the angle of the bend centre. Although there is no scour for flow intensities less than 0.55, the equilibrium depth of scour increases almost linearly with an increasing of the flow intensity and attains the maximum value of scour at a depth when the dimensionless approach velocity is equal to 1.0. The equilibrium depth of scour also increases while the dimensionless parameters such as side-weir length, side-weir height and flow shallowness increase. In a curved channel, the equilibrium depth of scour has the maximum value at 30 degrees and the minimum value at 120 degrees and 150 degrees sections of the bend depending on the direction of the path of maximum velocity which is affected momentum remaining in the main channel. Copyright (c) 2005 John Wiley & Sons, Ltd.
Keywords: side-weir; threshold velocity; secondary circulation; clear-water scour depth; curved flow; DISCHARGE COEFFICIENT; LOCAL SCOUR; FLOW; CHANNEL; Agriculture; Water Resources